Students' Perspectives on Zoom-Based Learning in Islamic Religious Education at UIN Sulthan Thaha Saifuddin Jambi - Yanri Ramdhano (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2025)
This study investigates the perspectives of Islamic Religious Education students at UIN Sulthan Thaha Saifuddin Jambi regarding online learning through Zoom. Using a descriptive qualitative approach, data were collected from ten students through open-ended questionnaires. The findings reveal that while students appreciated the flexibility, time efficiency, and accessibility provided by Zoom, they also experienced challenges such as unstable internet connections, reduced interaction, emotional fatigue, and diminished spiritual engagement. Understanding of course materials varied among students, with some benefiting from flexible access to content, while others struggled with abstract and value-based lessons. Ethical issues, including discipline and sincerity, were also affected in the online environment. Despite these challenges, many students remained motivated by personal goals and lecturer support. The study highlights that Zoom facilitates certain aspects of learning but cannot fully replace the depth of spiritual, ethical, and interpersonal connections inherent in traditional Islamic education. Students offered valuable suggestions for improving online learning, emphasizing the need for more interactive teaching methods and better infrastructure support. These insights underscore the importance of designing spiritually responsive and pedagogically engaging online religious education environments.